Nesiritide protects endothelial function after balloon-induced trauma in the iliac artery in rabbits - Shu-Qin Liu; Li-Ping Zhang; Huan-Ying Yan; Xing-Hua Zhang; Le-Xin Wang (Universidade de São Paulo, 2020)
To assess the effect of nesiritide on the endothelial function of iliac arteries following endothelia trauma. Right iliac artery trauma was created with a balloon catheter. Ten rabbits were treated with a 4-week subcutaneous injection of nesiritide at a fixed daily dose of 0.1mg/kg. Ten rabbits received daily normal saline injection. Plasma endothelin 1 (ET-1), nitric oxide (NO), and Von Willebrand Factor (vWF) were measured before and after the therapies. Tissue proliferating cell nuclear antigen (PCNA) was measured after the treatment. After the treatment, in the therapeutic group, the area under internal elastic membrane and the residual lumen area were higher than in the normal saline group (P <0.05). The plasma levels of ET-1 (91.6±6.8 vs 114.9±6.3 ng/L, P =0.001), vWF (134.6±10.8% vs 188.8±10.4%, P =0.001) and the ratio of PCNA positive expression (11.7±4.2% vs 36.2±11.4%, P =0.005) in the therapeutic group was lower than in the normal saline group, while the plasma levels of NO was higher (89.7±9.3 vs 43.5±5.3 µmol/L, P =0.001). Nesiritide inhibited remodeling of rabbit iliac artery following endothelial trauma. The inhibition of vascular remodeling may be related to the alleviated endothelial dysfunction and reduced expression of tissue proliferating cell nuclear antigen.